Strategic Management Reform at the Local Zakat Administration of South Sumatra, Indonesia - Hartono, Haryani Santo (Center of Strategic Studies (PUSKAS) BAZNAS, 2023)
The National Board of Zakat Republic of Indonesia (BAZNAS), a government-owned zakat institution, has standardized a strategy for the nationwide zakat administration. It organizes annual zakat awards, recognizing the outstanding zakat institutions in managing zakat. BAZNAS Musi Rawas Regency is one of the zakat award recipients in 2022, marking its recognition for substantial contributions to the administration of zakat in South Sumatra, Indonesia. This study employs a qualitative method to explore the strategic management reformation that took place in the BAZNAS Musi Rawas Regency. Such reformation efforts in improving strategic management are of practical reference for other regional BAZNAS in Indonesia.